2002
DOI: 10.1901/jeab.2002.78-161
|View full text |Cite
|
Sign up to set email alerts
|

Observing Behavior: Effects of Rate and Magnitude of Primary Reinforcement

Abstract: Four experiments examined the free-operant observing behavior of rats. In Experiment 1, observing was a bitonic function of random-ratio schedule requirements for the primary reinforcer. In Experiment 2, decreases in the magnitude of the primary reinforcer decreased observing. Experiment 3 examined observing when a random-ratio schedule or a yoked random-time schedule of primary reinforcement was in effect across conditions. Removing the response requirement for the primary reinforcer increased observing, sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
1
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 28 publications
5
32
1
4
Order By: Relevance
“…The initial increases in observing obtained with increases in the response requirement for ethanol parallel those recently obtained under similar conditions with rats responding for food (Shahan 2002b). Lieberman (1972) also obtained a similar result in an observing-response procedure with monkeys responding for sucrose.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The initial increases in observing obtained with increases in the response requirement for ethanol parallel those recently obtained under similar conditions with rats responding for food (Shahan 2002b). Lieberman (1972) also obtained a similar result in an observing-response procedure with monkeys responding for sucrose.…”
Section: Discussionsupporting
confidence: 81%
“…decreases in rate of drug delivery) may appear to call into question the notion that observing is maintained by conditioned reinforcement. However, Shahan (2002b) showed that the initial increases in observing with increases in price of a primary reinforcer likely result from competition between observing and behavior related to the primary reinforcer (e.g. primary reinforcer responding, hopper related behavior, post-ingestive behavior; cf.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shahan (2002) examined the effects of variations in rate of primary reinforcement on observing- Fig. 1.…”
Section: Behavioral Momentum Theorymentioning
confidence: 99%
“…This assumption cannot be supported directly because attending is measurable only by inference from a model. However, indirect support comes from research on observing behavior, which is widely construed as an overt, measurable expression of attending and which was related to reinforcement and disruption in the same way as suggested by Equation 4 (Shahan, 2002;Shahan et al, 2003).…”
Section: Core Assumptionsmentioning
confidence: 99%